Antioxidant Activity and Polyphenols Characterization of Four Monovarietal Grape Pomaces from Salento (Apulia, Italy) - Carmine Negro; Alessio Aprile; Andrea Luvisi; Luigi De Bellis; Antonio Miceli (MDPI AG, 2021)
The wine industry annually produces millions of tons of by-products rich in polyphenolic compounds that can be reused as secondary raw material in the food, cosmetic and pharmaceutical industries. The purpose of this work was to describe the presence of nutraceutical compounds and to evaluate the antioxidant activity of pomaces from three Apulian (South Italy, Italy) grape varieties (Negroamaro, Malvasia di Lecce and Primitivo) and to compare them with one of the most cultivated wines in Europe (Cabernet Sauvignon). The main classes of polyphenolic substances were characterized via high performance liquid chromatography/diode array detector/mass spectrometer time of flight (HPLC/DAD/TOF) and the antioxidant activity was evaluated with three different methods. The four investigated grape marcs have shown different polyphenols and antioxidant activities. Primitivo marc showed the higher antioxidant activity due to the excellent level of polyphenols, followed by the Negroamaro cultivar. In addition, marcs from traditional Apulian vines showed higher antioxidant activities than Cabernet Sauvignon because of an elevated level of active polyphenolic substances such as catechin, epicatechin, quercetin and its derivatives.